2020
DOI: 10.1007/s11075-020-01004-6
|View full text |Cite
|
Sign up to set email alerts
|

Linearized Krylov subspace Bregman iteration with nonnegativity constraint

Abstract: Bregman-type iterative methods have received considerable attention in recent years due to their ease of implementation and the high quality of the computed solutions they deliver. However, these iterative methods may require a large number of iterations and this reduces their usefulness. This paper develops a computationally attractive linearized Bregman algorithm by projecting the problem to be solved into an appropriately chosen low-dimensional Krylov subspace. The projection reduces the computational effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…It is a well known result, and it is illustrated in [57] that in the context of Tikhonov regularization with the regularization parameter determined by the discrepancy principle that the quality of the computed solution may be increased by carrying out a few more iterations of the Arnoldi process. A similar observation was concluded in [17] as well that adding few more vectors in the subspace after the discrepancy principle is satisfied enhances the quality of the computed solution. In this work, we stop the iterations using the discrepancy principle.…”
Section: Solving the Problem In The Subspace Generated By Fgksupporting
confidence: 79%
See 1 more Smart Citation
“…It is a well known result, and it is illustrated in [57] that in the context of Tikhonov regularization with the regularization parameter determined by the discrepancy principle that the quality of the computed solution may be increased by carrying out a few more iterations of the Arnoldi process. A similar observation was concluded in [17] as well that adding few more vectors in the subspace after the discrepancy principle is satisfied enhances the quality of the computed solution. In this work, we stop the iterations using the discrepancy principle.…”
Section: Solving the Problem In The Subspace Generated By Fgksupporting
confidence: 79%
“…where among different choices of L are discretization of the first or the second derivative operator, framelet or wavelet transforms [15,17], or a weighting matrix aiming to reconstruct solutions with certain properties. For instance, if is chosen to be a transformation operator to the framelet domain, then by minimizing (3.13) with 0 < p ≤ 1 we seek to reconstruct solutions with sparse representation in the transformed framelet domain.…”
Section: The Minimization Problemmentioning
confidence: 99%
“…We have shown that the proposed method outperforms the classical TV approach. Matter of future research include the application of the proposed method to more general inverse problems as well as the integration of the considered method with the ℓ p − ℓ q minimization proposed in [12,[14][15][16]32,36] or with iterative regularization methods like, e.g., Linearized Bregman splitting [11,13,[18][19][20] and Iterated Tikhonov with general penalty terms [3,4,7,10]. Another line of future research is the construction of more sophisticated graphs ω which can better exploit the structure of the given image itself.…”
Section: Discussionmentioning
confidence: 99%
“…Nonnegativity constraint. In many application, such as medical imaging and astronomical imaging, the pixels of the desired solution are nonnegative [7,8,28], that is, the exact solution of (1.3) is known to live in the closed and convex set Ω 0 = {u ∈ R n : u ≥ 0, = 1, 2, . .…”
Section: Iterative Methods and Parameter Selection Techniquesmentioning
confidence: 99%